Respiratory Chain Complex I Deficiency in Leber Hereditary Optic Neuropathy: Insights from Ophthalmologic and Molecular Investigations in Tunisia - Latifa Chkioua; Yessine Amri; Chayma Sahli; Tawfik Nasri; Mohamed Omar Miladi; Taieb Massoud; Sandrine Laradi; Mohamed Ghorbel; Hassen Ben Abdennebi (BMC Genomics)
Abstract Background Leber hereditary optic neuropathy (LHON) is a mitochondrial DNA (mtDNA) rare disease due to the pathogenic variant of the NADH dehydrogenase enzyme. LHON is characterized by a sudden central vision loss due to focal degeneration of the retinal ganglion cell layer and optic nerve. Symptoms usually appear between the age of 18 and 35 years. Some individuals present the mtDNA mutations but not presented the LHON clinical features. The heteroplasmic or homoplasmic character of the mutations among patients explains why they develop the disease or not even though they carry the pathogenic variant. Methods This study was performed in collaboration with the department of ophthalmology of Farhat Hached Hospital, Sousse, Tunisia. Screening for the common mutations in Mt-ND1 gene (m.3460G > A), Mt-ND4 gene (m.11778G > A) and Mt-ND6 gene (m.14484T > C) was performed in five Tunisian families by standard RFLP PCR, followed by direct sequencing of the entire of these genes. Indeed, bioinformatics tools were used to predict the potential functional impact of the identified mutations on the Human mitochondrial respiratory complex I protein. Results one novel p.L601M (m.1413 C > A) and four previously reported mutations were identified in this study including: rs199476112G > A (m.11778G > A); rs202227543G > A (m.14258G > A); rs1603224763 (m.14510 dup) and NC_012920.1: m.3244G > C. In this present report, only one patient was found carrying the primary point mutation (m. 11778G > A). The ophthalmologic findings showing major fundus changes included hyperemic optic discs; disc pseudo-oedema and microangiopathy leading to optic disc atrophy. The analyses of the stability of protein upon identified mutations using DynaMut tool server demonstrated that these variations induce a rigidification in the region where they are located. Conclusion This is the first Tunisian report of mtDNA mutations identified in Tunisia causing the LHON. The main factors involved in the pathophysiological mechanisms of this disease are genetic, epigenetic, hormonal and environmental influences.